"PENOPLEX" THERMAL INSULATION PLATES AND THEIR AREAS OF APPLICATION (Spectrum Journal of Innovation, Reforms and Development, 2024)
Penoplex" thermal insulation plates are made by extrusion of polystyrene. The process of extrusion of polystyrene makes it possible to create a foamed material with a homogeneous structure composed of closed pores with a size of 0.1-0.2 mm. This article provides information about "Penoplex" thermal insulation boards and their areas of application.